Moral submissiveness: social origin as a vulnerability for well-being on a warming planet - Weihgold, Vanessa (Frontiers in Psychology, 2024)
In recent years, the emotional experience of climate change has been studied extensively from fields like psychology, theology, sociology, and philosophy. It is crucial to analyze these results for possible vulnerability with regard to well-being. While climate justice research raises awareness of the current (social) situation of the participants in relation to the experience of climate change, the research on climate emotions seems to overlook the participant’s former social situation – their family of origin. Previous studies on injustice have shown however that it is precisely the way people were educated on emotion work that has a significant impact on their experiences and sense of control in the situation. Given the importance of this sense of control for mental well-being, I argue consequently that social origin is a vulnerability for well-being in the (emotional) experience of climate change, perpetuating climate injustice, based on this combination of studies from different epochs. Therefore, in the interest to protect well-being on a warming planet, it is crucial to raise awareness of the impact of social origin.